2011
DOI: 10.1016/j.ejvs.2011.05.014
|View full text |Cite
|
Sign up to set email alerts
|

DynaCT in Pre-treatment Evaluation of Aortic Aneurysm before EVAR

Abstract: The result indicates that DynaCT gives sufficient information to determine the correct treatment and for selecting the proper stent graft before EVAR. A limited volume size reduces the evaluation of the iliac arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…From a clinical viewpoint, the choice, usage, benefit, and limitations of ceCBCT as an immediate 3D control of an interventional procedure is well documented in the literature, though mainly with regards to image quality, added clinical value, and additional patient contrast dose. 1,5,8,11,12,21 23 A recent publication by Törnqvist et al 1 compares conventional angiography (CA), 3-phase MDCT, and ceCBCT with regard to the detection of endoleaks. They demonstrated that combining CA and CBCT provides the same relevant clinical information as follow-up MDCT examinations 1 month after intervention, making MDCT angiography “unnecessary in some patients.” As an alternative during or after EVAR, other modalities could be included, such as ultrasound or magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical viewpoint, the choice, usage, benefit, and limitations of ceCBCT as an immediate 3D control of an interventional procedure is well documented in the literature, though mainly with regards to image quality, added clinical value, and additional patient contrast dose. 1,5,8,11,12,21 23 A recent publication by Törnqvist et al 1 compares conventional angiography (CA), 3-phase MDCT, and ceCBCT with regard to the detection of endoleaks. They demonstrated that combining CA and CBCT provides the same relevant clinical information as follow-up MDCT examinations 1 month after intervention, making MDCT angiography “unnecessary in some patients.” As an alternative during or after EVAR, other modalities could be included, such as ultrasound or magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
“…4 The development of intra-operative cross sectional imaging techniques such as cone beam computed tomography (CBCT) have been shown to be feasible both in EVAR planning and as completion imaging to detect complications missed by conventional angiography. 5,6 The aim of this study was to evaluate the efficacy of completion CBCT in detecting intra-operative complications compared with standard final angiography. In addition, completion CBCT was compared with the 1 month CTA to evaluate the use of CBCT alone as the primary modality for early post-operative imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies focused on visualizing insufficiently radiopaque foreign material or devices and their 3D relationships to the vasculature or peripheral soft tissues, including embolic material in head and neck tumor embolizations16 and intrahepatic chemoembolization 17. Both preoperative planning for endovascular aortic stent graft repair18 and postprocedure evaluations to assess carotid and cerebrovascular stent apposition have been described 19. Additionally, high contrast resolution, enabling visualization of the intracranial compartment and soft tissues, is a valuable tool for rapidly recognizing serious intraprocedural complications such as intracranial hemorrhage 14 19–24.…”
Section: Discussionmentioning
confidence: 99%